Phytochemical Features of Turmeric in Folk and Traditional Medicine (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The chemical composition of turmeric consists of approximately 70% carbohydrates, 13% moisture, 6% protein, 6% essential oils (phellandrene, sabinene, cineole, borneol, zingiberene and sesquiterpenes), 5% fat, 3% minerals (potassium, calcium, phosphorus, iron and sodium), 3-5% curcuminoids and trace amounts of vitamins (B1, B2, C and niacin). Extracts of C. longa and its constituent, curcumin, have demonstrated a relaxing effect on tracheal smooth muscle, indicating their bronchodilator effect in obstructive pulmonary diseases.